The financial inclusion in Peru - Vargas Garcia, Allan Herminio (2021)
Financial inclusion is a key factor in the economic development of a nation from the point of view of access (supply), use (demand) and quality of financial services. The use and access to financial services allows the population to save surplus capital to make forecasts and future investments. Likewise, it generates a solid base of savings reducing dependence on international financial markets in the face of economic shocks. Access to an account in the financial system is the principle of financial inclusion. In the world, 68% of adults have access to an account; However, only 55% keep their account active (real access), from which a significant percentage of inactive accounts can be deduced. In Peru, 43% of adults have an account at a bank or other type of financial institution. To achieve development in financial inclusion, not only the increase in the number of active accounts must be taken into account, but also a greater use of financial services such as: payments, transfers, savings, credit and insurance.